Penerapan Fuzzy Logic untuk Menentukan Minuman Susu Kemasan Terbaik dalam Pengoptimalan Gizi - Auliah Khoirun Nisa; Muhammad Abdy; Ahmad Zaki (Jurusan Matematika FMIPA UNM, 2020)
This applied research aims to build a model of determining the best packaged milk with consideration variables are price and nutrition. The steps used in this research are fuzzification, fuzzy rule determination, fuzzy inference with mamdani method, and defuzzification. The data used are data taken from direct field surveys conducted by researchers in one of the supermarkets in Makassar. The results of this study is sample 16 packaged milk which is the most suitable packaged milk to recommended because it has high nutrition and affordable prices.